Post Disaster Stimulant Fund Distribution Management In Mamboro Village, Palu City - Nurhayati Hamid; Arlitha Puspita Sari (Journal of Public Administration and Government, 2023)
After the disaster, many houses were badly damaged, leaving residents without proper housing. Management of stimulant funds for post-disaster damaged houses is a crucial part of community recovery efforts after natural disasters. In the post-disaster situation, many houses suffered serious damage, leaving residents without proper shelter. Stimulant funds are used to provide financial assistance to people whose homes have been damaged in order to repair or rebuild their homes. This study aims to determine the implementation of the management of the distribution of stimulant funds for damaged houses for victims of natural disasters in the Mamboro Village. This research method is Qualitative. From the results of the study it can be concluded that the planning that was carried out was not fully mature because in the process of collecting data, invalid and inaccurate data were found, such as the discovery of duplicate data. Meanwhile, the movement has not run optimally because the process takes a long time.